Taxation, Industry Integration and Production Efficiency - Simone Moriconi (Center for Economic Studies and ifo Institute (CESifo), 2016)
Taxes levied on production processes (e.g. VAT), are today a very important source of government revenues in developed economies. Theories of optimal taxation conclude that these taxes are detrimental to production efficiency, when firms operate in perfectly competitive markets. These theories draw on the neoclassical approach, which regards firms as single production units. The present paper investigates the effects of taxation on production efficiency, accounting for the organization of an industry. The model shows that a lump-sum tax does not have any effect on the organization of the industry, while a non lump-sum tax can be designed that induces an organizational change of the industry. The paper shows that the effect of this ”tax induced organizational change” on production efficiency ultimately depends on the characteristics of the market.
Keywords: H21; L22; H32; 330; taxation; organizational change; vertical integration; production efficiency